Growth Factor Receptor Bound Protein 2–Associated Binder 2, a Scaffolding Adaptor Protein, Negatively Regulates Host Immunity against Tuberculosis - Hu, Shizong; Zhang, Yan; Yu, Yang; Jin, Dongdong; Zhang, Xue; Gu, Shuxiang; Jia, Hongyan; Chen, Xinchun; Zhang, Zongde; Jin, Qi; Ke, Yuehai; Liu, Haiying (American journal of respiratory cell and molecular biology, 2014)
Cell-mediated immunity is indispensable for host protection against tuberculosis (TB). Growth factor receptor bound protein 2-associated binder (Gab) 2, a scaffolding adaptor protein, negatively regulates signaling pathways critical for T cell-mediated immunity. We sought to investigate the clinical significance and immunological role of Gab2 in Mycobacterium tuberculosis infection. We evaluated Gab2 protein and messenger RNA (mRNA) expression in human patients with pulmonary TB and determined the correlation of the mRNA expression pattern with antigen-specific IFN-γ secretion. Subsequently, we carried out M. tuberculosis infection in Gab2-deficient and wild-type control mice to explore the immunological role of Gab2 by examining bacterial load, histological changes, cytokine secretion, and gene expression of immune-associated transcription factors. mRNA levels of Gab2 and its correlated family member, Gab1, were markedly decreased in untreated patients with pulmonary TB compared with healthy control subjects. Importantly, this decreased Gab2 expression to normal levels after bacterial load in the patient's sputum became undetectable under the standard anti-TB treatment, which negatively correlated with the level of M. tuberculosis antigen-specific IFN-γ secretion. In the M. tuberculosis infection mouse model, infected Gab2-deficient mice exhibited decreased bacterial load and milder lung pathological damage compared with infected wild-type mice, accompanied by decreased production of IL-2, IL-6, and granulocyte/macrophage colony-stimulating factor proinflammatory cytokines, and an increased T-cell-specific T-box transcription factor/GATA binding protein 3 expression ratio. Overall, our study indicates that down-regulation of Gab2 relates to a protective function during M. tuberculosis infection, revealing a potential negative regulatory role for Gab2 in immunity to TB.